Public Legitimacy of Management Dismissal Decisions in the Social Media Era: The Viral Case of “Anita Tumbler” - Afiah Mukhtar; Herenal Daeng Toto; Rahmat Rahmat; Masradin Masradin; Rif'ah Shafwah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze how digital public reactions play a role in shaping the social legitimacy of management decisions to terminate employees in the social media era, using the viral case study of "Anita Tumbler." This research starts from the assumption that the legitimacy of termination decisions is no longer solely determined by formal organizational procedures. Methods: this study used a qualitative approach through content analysis of comments from netizens on social media related to the case, as well as document analysis of the company's official response. Data were analyzed using NVivo 12 software to identify dominant themes, patterns of public reactions, and organizational legitimacy. Results: the results indicate that public reactions in the digital space were dominated by public anger, moral judgment, justification of punishment, and ridicule. These patterns collectively construct a normative narrative that legitimizes the termination decision as a socially acceptable action. The findings also reveal that the legitimacy of termination decisions is shaped by public opinion and emotional responses in the digital space rather than solely through legal grounds or formal procedures. Implications: this study emphasizes the importance of balancing the protection of employee freedom of expression with professional obligations in the use of social media. In the era of social media, HR is not only required to be able to respond to public pressure, but also to consider the proportionality of sanctions, the long-term impact on individuals, and justice mechanisms that protect both parties, namely the organization and the employees themselves.